Evaluation of Medical Management of Phimosis in Pediatric Patients: A Descriptive Cross Sectional Study - Bajracharya, Jasmine; Thapa, Bineet; Oli, Kaushal; Lamichhane, Deepika; Shrestha, Rit (Nepal Medical College Journal, 2024)
Phimosis is considered virtually universal in newborn males. Circumcision is mostly done for unresolved phimosis. There is a stream of evidence that suggests steroid cream application is effective in these children prior to any surgical decision. A cross-sectional descriptive study from October 2021 to November 2022, was designed to include all cases of phimosis in male children up to 15 years of age. Caregivers of the patients were counseled and advised for management with hydrocortisone 1.0% ointment twice a daily and follow up in 2 weeks. The resolution rates were noted in 2 weeks and 4 weeks and unresolved children were counseled for either continuation of medical management or circumcision. Electronic registry was used to enroll all the cases and note the outcomes. A total of 146 boys were evaluated. Median age of presentation was 4 years, 113 children (77.4%) were successfully treated with medical therapy and only 33 children (22.6%) had failed medical therapy requiring circumcision. A total of 66 children (58.4%) required only 1 followup for resolution of phimosis. By contrast, 47 children (41.6%) required more than 1 follow-up for resolution. Topical steroid in treatment of phimosis is a very safe, effective, inexpensive and easy approach that attenuates the need for surgical intervention. The response rate is very high and adverse effects are minimal. In the developing world, medical therapy can thus be more feasible of an option as compared to surgery.